Traditional food availability and consumption in remote Aboriginal communities in the Northern Territory, Australia. (28th March 2017) - Ferguson, Megan; Brown, Clare; Georga, Claire; Miles, Edward; Wilson, Alyce; Brimblecombe, Julie
Abstract: Objective: To explore availability, variety and frequency consumption of traditional foods and their role in alleviating food insecurity in remote Aboriginal Australia. Methods: Availability was assessed through repeated semi‐structured interviews and consumption via a survey. Quantitative data were described and qualitative data classified. Results: Aboriginal and non‐Indigenous key informants (n=30 in 2013; n=19 in 2014) from 20 Northern Territory (NT) communities participated in interviews. Aboriginal primary household shoppers (n=73 in 2014) in five of these communities participated in a survey. Traditional foods were reported to be available year‐round in all 20 communities. Most participants (89%) reported consuming a variety of traditional foods at least fortnightly and 71% at least weekly. Seventy‐six per cent reported being food insecure, with 40% obtaining traditional food during these times. Conclusions: Traditional food is consumed frequently by Aboriginal people living in remote NT. Implications for public health: Quantifying dietary contribution of traditional food would complement estimated population dietary intake. It would contribute evidence of nutrition transition and differences in intakes across age groups and inform dietary, environmental and social interventions and policy. Designing and conducting assessment of traditional food intake in conjunction with Aboriginal leaders warrants consideration.